Tanggung Jawab Instansi Atas Kerugian Immateril Terhadap Wiraswasta Akibat Adanya Pengadaan Tanah Untuk Kepentingan Umum - Amira Karana Sharira Yuan; Widhi Handoko (Magister Kenotariatan Universitas Diponegoro, 2022)
AbstractLand acquisition for public interest carried out by the government must be accountable to the parties that have been harmed, the responsibility is in the form of compensation for material and immaterial losses. The research method used by this journal is normative research. The results of the discussion of this journal are the government's responsibility in terms of land acquisition for the public interest of entrepreneurs, namely in the form of material compensation and immaterial damages based on Law Number 2 of 2012, Indonesian Assessment Standards (SPI) Number 204 of 2018 and other regulations as well as 6 (six) principles of land acquisition. The conclusion from the discussion of this journal is that in reality the government's responsibility for entrepreneurs in land acquisition for the public interest is only in the form of material compensation while non-physical or immaterial compensation has not been implemented, besides Law Number 2 of 2012 does not explicitly regulate immaterial compensation .Keywords: land acquisition; responsible; compensationAbstrakPengadaan tanah untuk kepentingan umum yang dilakukan oleh pemerintah harus bertanggung jawab kepada para pihak yang telah dirugikan, tanggung jawab berupa penggantian kerugian secara materiil dan immaterial. Metode penelitian yang digunakan oleh jurnal ini yaitu penelitian normatif. Hasil pembahasan jurnal ini adalah tanggung jawab pemerintah dalam hal pengadaan tanah untuk kepentingan umum terhadap wiraswasta yaitu berupa ganti rugi secara materiil dam immaterial yang didasarkan pada Undang-Undang Nomor 2 Tahun 2012, Standar Penilaian Indonesia (SPI) Nomor 204 Tahun 2018 dan peraturan lainnya serta 6 (enam) prinsip pengadaan tanah. Kesimpulan dari pembahasan jurnal ini bahwa pada kenyataannya tanggung jawab pemerintah terhadap wiraswasta dalam pengadaan tanah untuk kepentingan umum hanya berbentuk ganti rugi secara materiil sedangkan non fisik atau immaterial belum dilaksanakan, selain itu Undang-Undang Nomor 2 Tahun 2012 tidak mengatur secara tegas mengenai ganti rugi immaterial.Kata Kunci: pengadaan tanah; tanggung jawab; ganti rugi